1986
DOI: 10.1051/agro:19860407
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the final stage in seed abortion in indeterminate soybean, white lupin and pea

Abstract: A final stage in seed abortion has been identified by Japanese studies on soybeans (G I .v-c-iiie iiiu.B (L.) Merril). It is a significant stage in the development of the yield components and it may be useful in a pod development scale. To find a simple characterization of this stage, the seeds of 26 samples of aborted plus ripe seeds at harvest were first measured and weighed. Twenty samples were of indeterminate soybean (10 cultivars), 4 of white lupin, Lupinus albus L. (4 cultivars), and 2 of pea, Pisum sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…This is consistent with previous reports of the effects of disease occurring on the whole plant or on the vegetative parts of the plant (Garry et al, 1996. This critical stage, defined as such by Pigeaire et al (1986) for healthy plants and observed in conditions of abiotic stress (water supply deficiency, e.g. Ney, Duthion & Turc (1994)).…”
Section: Seed Number and Isw As A Function Of Diseasesupporting
confidence: 92%
“…This is consistent with previous reports of the effects of disease occurring on the whole plant or on the vegetative parts of the plant (Garry et al, 1996. This critical stage, defined as such by Pigeaire et al (1986) for healthy plants and observed in conditions of abiotic stress (water supply deficiency, e.g. Ney, Duthion & Turc (1994)).…”
Section: Seed Number and Isw As A Function Of Diseasesupporting
confidence: 92%
“…This corresponds to evidence that seed number per square meter is related to canopy photosynthesis during the same period (e.g., Heitholt et al, 1986; Egli et al, 1985; Jones et al, 1984; Egli and Yu, 1991). Seed number per square meter is determined prior to the period of linear seed growth for any particular pod (Pigeaire et al, 1986; Duthion and Pigeaire, 1991). The sequential fruiting characteristic of soybean results in a range of developmental stages of reproductive organs on the same plant (e.g., Spaeth and Sinclair, 1984a).…”
Section: Discussionmentioning
confidence: 99%
“…During seed set, seed abortions can occur. At the end of this first period, called the final stage in seed abortion (Pigeaire et al, 1986), the final seed number of the pod is fixed. The total seed number per stem is fixed when the last pod of the stem reaches this stage.…”
Section: Methodsmentioning
confidence: 99%